Drug release from liposome coated hydrogels for soft contact lenses: the blinking and temperature effect - Paradiso, P. (2017)
In this article, liposome-based coatings aiming to control drug release from therapeutic soft contact lenses (SCLs) materials are analyzed. A PHEMA based hydrogel material loaded with levofloxacin is used as model system for this research. The coatings are formed by polyelectrolyte layers containing liposomes of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) and DMPC + cholesterol (DMPC + CHOL). The effect of friction and temperature on the drug release is investigated. The aim of the friction tests is to simulate the blinking of the eyelid in order to verify if the SCLs materials coated with liposomes are able to keep their properties, in particular the drug release ability. It was observed that under the study conditions, friction did not affect significantly the drug release from the liposome coated PHEMA material. In contrast, increasing the temperature of release leads to an increase of the drug diffusion rate through the hydrogel. This phenomenon is recorded both in the control and in the coated samples.